Consistency of the Moreau CLL score. Issue 5 (28th December 2017) - Sorigue, Marc; Sarrate, Edurne; Franch‐Sarto, Mireia; Feliu, Evarist; Junca, Jordi
Abstract : Background: The Moreau score is essential for the diagnosis of B‐cell lymphoproliferative disorders (B‐LPD). Methods: We assessed the consistency of the Moreau score in a series of 138 patients with at least two samples involved by a B‐LPD (316 samples) other than germinal center‐derived malignancies, hairy cell leukemia, and mantle cell lymphomas. Patients with evidence of two distinct B‐LPDs were also excluded. Results: We found 53 inconsistencies in 44 of 138 (32%) patients. FMC7 was the most inconsistent (18 cases) and CD5 the least (5 cases). CD200 was inconsistent in 6 of 67 (9%) cases. The most important predictive factor for the finding of antigenic inconsistencies was sampling of a different anatomic site. Other factors, including number of samples, time between samples, or cytogenetic group, were not predictive. For the most part, these inconsistencies did not appear to be clinically relevant. Conclusion: Inconsistencies in the Moreau score are common, supporting the importance of integrated laboratory diagnosis. However, the practical implications of these antigenic inconsistencies are probably limited.